Catalyst for synthesizing alkyl mercaptan and preparation method thereof
By using catalysts with support as titanium dioxide, zirconium dioxide and alkali metal oxides as cocatalysts, the problem of difficult to improve the activity and selectivity of the methanol thiolation reaction catalyst in the prior art is solved, and the catalytic effect with high selectivity and activity is achieved, and the preparation process of the catalyst is simplified.
Patent Information
- Application Number
- CN202080026148.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-01-29
- Filing Date
- 2020-01-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2040-01-27
Smart Images

Figure BDA0003286464490000111 
Figure BDA0003286464490000121 
Figure BDA0003286464490000141
Abstract
Description
[0001] The present invention relates to a TiO2 and / or ZrO2 based catalyst for preparing alkyl mercaptan and a method for preparing the same. The present invention also relates to a method for preparing alkyl mercaptan by reacting an alkyl alcohol with hydrogen sulfide in the presence of a supported catalyst according to the present invention or in the presence of a catalyst obtained by the method for preparing the same according to the present invention.
[0002] Alkyl mercaptan is an industrially important intermediate for the preparation of products with high economic value. In particular, methyl mercaptan (CH SH) is an industrially important intermediate, for example in the synthesis of methionine, dimethyl sulfoxide, dimethyl sulfone or methanesulfonic acid. In the past, a variety of different synthetic routes have been developed, for example, the hydrogenation of carbonyl sulfide (COS) or carbon disulfide (CS ), the mercaptation of methanol with CS in the presence and absence of H , and the mercaptation of methanol with hydrogen sulfide (H S) as a mercaptation agent in the presence of an alumina-based catalyst. The latter method represents the current industrial state of the art method, which is usually carried out in the gas phase at a temperature of 300 to 500 ° C and a pressure of 1 to 25 bar.
[0003] The reaction mixture thus obtained contains the desired product methyl mercaptan as well as unreacted starting materials and by-products, such as dimethyl sulfide and dimethyl ether, and gases inert to the reaction, such as methane, carbon monoxide, hydrogen and nitrogen. Therefore, the methyl mercaptan formed must be separated from the reaction mixture.
[0004] The separation of methyl mercaptan from the gaseous reaction mixture is usually carried out by condensation of methyl mercaptan. Here, the energy consumption for cooling the reaction mixture is a significant cost factor. Therefore, for good economic efficiency of the process, it is necessary to form methyl mercaptan with high conversion and high selectivity in order to keep the energy input and investment costs as low as possible.
[0005] Improvements in activity and selectivity can be obtained by increasing the molar ratio of hydrogen sulfide to methanol. Molar ratios between 1 and 10 are usually used. However, high molar ratios also mean a high excess of hydrogen sulfide in the reaction mixture, so that large amounts of gas need to be circulated. In order to reduce the energy input required for this, the ratio of hydrogen sulfide to methanol should therefore deviate only slightly from 1.
[0006] In order to improve the activity and selectivity, specific Al2O3-based catalysts have been designed. It is generally believed that aluminum oxide, especially γ-Al2O3, is in principle a catalyst for the mercaptation of methanol to obtain methyl mercaptan. However, the activity of aluminum oxide is too high, so the catalytic reaction does not stop at the desired product methyl mercaptan. More precisely, the very active aluminum oxide also catalyzes the further reaction of methyl mercaptan to form dimethyl sulfide. Therefore, aluminum oxide is usually mixed with an alkali metal tungstate such as potassium tungstate or cesium tungstate to reduce its activity, which leads to an increase in the selectivity for the formation of methyl mercaptan and a decrease in the selectivity for the formation of by-products such as dimethyl sulfide. In the catalyst thus obtained, aluminum oxide is also called a carrier or catalyst carrier, and the alkali metal tungstate is called a co-catalyst. The proportion of tungstate is usually up to about 20% by weight, based on the total weight of the catalyst, as described in U.S. Patent No. 2,820,062. The catalyst disclosed in this document provides good activity and selectivity in the production of alkanethiols at a reaction temperature of 400°C and a molar ratio of hydrogen sulfide to alkyl alcohol of 2:1.
[0007] In a relatively complex preparation process involving multiple impregnations of the support material with an alkali tungstate solution, the proportion of alkali tungstate in the catalyst can be increased to 25% by weight or more. U.S. Pat. No. 5,852,219 discloses the advantages of using cesium tungstate (Cs2WO4) instead of potassium tungstate (K2WO4) as a promoter. Thus, increased activity can be obtained simultaneously with good selectivity. According to Mashkina et al. (React. Kinet. Catal. Lett., Vol. 36, No. 1, 159-164 (1988)), the best selectivity for forming alkyl mercaptans from alkyl alcohols and hydrogen sulfide is achieved with a catalyst having an alkali / tungsten ratio of 2:1. Impregnation of an alumina support with a solution containing cesium and tungsten in a stoichiometric ratio of 2:1 allows the realization of promoter loadings of up to 40% by weight based on the total weight of the catalyst, as described in U.S. Pat. No. 5,852,219. Increasing the concentration of alkali tungstate to 25% by weight or more results in an increased selectivity for forming methyl mercaptan. However, a disadvantage is that the activity of the catalyst is reduced at the same time.
[0008] As described in U.S. Patent Application 2009 / 306432 A1, multiple impregnations of the support material with a solution containing cesium and tungsten in a non-stoichiometric ratio of less than 2:1 allow the loading of the catalyst and the promoter to be increased to a value of 25% by weight or more based on the total weight of the catalyst. Although the loading of aluminum and the promoter can be increased to more than 35% by weight by using non-stoichiometric cesium and tungsten in the impregnation solution, there is no longer a significant increase in activity or selectivity at such high loadings. In particular, the activity and selectivity even decrease with a loading above 45% by weight based on the total weight of the catalyst. Another disadvantage is that the catalyst produced by the multiple impregnation method does not have a uniform distribution of cesium and tungsten throughout the catalyst body. However, in order to achieve high activity and high selectivity in the catalytic reaction, it is believed that the catalytically active components must be uniformly distributed throughout the catalyst body.
[0009] U.S. Patent Application 2014 / 357897 A1 discloses a catalyst in which alkali metals and tungsten are evenly distributed throughout the catalyst molding. These catalysts are produced by mixing a carrier material with an oxidizing tungsten material such as tungstic acid and at least one separate alkali metal compound such as cesium hydroxide to obtain a catalyst material, which is then molded. The catalyst thus obtained has a promoter loading of 45% by weight or more based on the total weight of the catalyst. This allows further improvement in the yield and selectivity of forming methyl mercaptan. However, the high yield and selectivity of the catalyst cannot last long and are therefore not suitable for use in industrial processes.
[0010] WO 2017 / 114858 A1 discloses another method for preparing a catalyst for preparing alkanethiols. This preparation method represents a combination of a common impregnation procedure and a mixing or shaping method of US patent application 2014 / 357897 A1. The activity and methyl mercaptan selectivity of the catalyst thus obtained are comparable to those of other catalysts. However, the rather complicated preparation method does not bring about an improvement in performance.
[0011] As mentioned above, considerable efforts have been made to improve the activity and selectivity of catalysts for the mercaptation of methanol. However, the catalyst host system does not seem to allow any further improvement in the mercaptation of methanol. Therefore, the problem to be solved is to provide an improved catalyst for the mercaptation of methanol, which has an improved selectivity compared to the catalysts of the prior art.
[0012] Surprisingly, it has been found that this problem is solved by using a catalyst support which is different from the supports of the prior art. This particular catalyst support is loaded with an alkali metal oxide.
[0013] An object of the present invention is therefore a catalyst comprising or consisting of a support and 5 to 20% by weight of a promoter, based on the total weight of the catalyst, wherein the support comprises or consists of titanium dioxide, zirconium dioxide and / or mixtures thereof and the promoter is an alkali metal oxide.
[0014] Deviations from the content of 5-20% by weight of the co-catalyst, based on the total weight of the catalyst, are still within the scope of the present invention as long as they still result in the effects of the present invention.
[0015] According to the present invention, the carrier of the catalyst comprises titanium dioxide, zirconium dioxide and / or their mixture, or is composed of them. Therefore, the carrier does not necessarily have to be composed of titanium dioxide, zirconium dioxide and / or their mixture. This takes into account the situation that the material still contains adhesives, fillers or any other components from its production. However, the main amount of material independent of this should be titanium dioxide, zirconium dioxide and / or their mixture. Preferably, the carrier of the catalyst comprises at least 50% by weight, in particular 55-100% by weight, 60-100% by weight, 65-100% by weight, 70-100% by weight, 75-100% by weight, 80-100% by weight, 85-100% by weight, 90-100% by weight or 95-100% by weight of titanium dioxide, zirconium dioxide and / or their mixture. In extreme cases, the carrier is composed of titanium dioxide, zirconium dioxide and / or their mixture.
[0016] The support materials according to the invention differ from the supports of the prior art not only in their elemental composition but also in their structure. They contain or consist of a tetragonal phase. In contrast, pure γ-Al2O3 as a catalyst support in the prior art has a cubic phase.
[0017] In one embodiment, at least a portion of the support of the catalyst according to the present invention has a tetragonal phase. Preferably, the support of the catalyst according to the present invention consists of a tetragonal phase.
[0018] The catalysts of the prior art usually contain alkali metal tungstates as promoters. However, it has been found that alkali metal tungstates are not necessarily required to provide catalysts with the desired selectivity for forming alkyl mercaptans in the alkyl alcohol thiolation reaction. Rather, it is sufficient to use alkali metal oxides as promoters. In the start-up phase of the catalyst, the alkali metal oxide is sulfided.
[0019] In principle, the invention is not limited to the choice of a specific alkali metal of the promoter. The alkali metal can therefore be any known alkali metal, preferably sodium, potassium, cesium or rubidium. However, cesium is the alkali metal that most improves the selectivity of the catalyst.
[0020] In a further embodiment of the catalyst according to the invention, the alkali metal is therefore sodium, potassium, cesium or rubidium.
[0021] In another embodiment of the catalyst according to the invention, the promoter is cesium oxide.
[0022] Compared with the catalysts of the prior art, the Cs-loaded catalysts according to the present invention provide a significant improvement in the selectivity for methyl mercaptan. For the ZrO2-based catalyst with 10 wt% Cs loaded, the selectivity for methyl mercaptan increased to S CH3SH,300℃ =99.9% to S CH3SH,360℃ =99.1% range. The only by-product found was S DMS,300℃ =0.1% to S DMS,360℃ = 0.9% dimethyl sulfide. Increasing the Cs loading to 20 wt% results in a CH3SH,300℃ =99.9% and S CH3SH,360℃ =99.4% or even higher selectivity. Similar results were found for TiO2-based catalysts: in the case of 10 wt% Cs, the selectivity for methyl mercaptan increased to between S CH3SH,300℃ =99.9% to S CH3SH,360℃ =99.4%. Again, the only byproduct found was S DMS,300℃ =0.1% to S DMS,360℃ = 0.6% dimethyl sulfide. Increasing the Cs loading to 20 wt% again resulted in a CH3SH,300℃ =99.9% and S CH3SH,360℃ =99.5% or even higher selectivity. The selectivity of methyl mercaptan achieved by the catalyst according to the invention is higher than the selectivity of methyl mercaptan achieved by the catalyst of the prior art by more than 2% in absolute value. In contrast, the best catalyst of WO 2013 / 092129 A1 provides a selectivity of methyl mercaptan of at most 97.9%.
[0023] The catalyst according to the invention comprises 5 to 20% by weight of promoter, based on the total weight of the catalyst. In the case where the catalyst is a shell catalyst, the amount of 5 to 20% by weight is related to the composition of the shell.
[0024] In principle, the catalyst according to the present invention is not limited in its shape. In its simplest form, the catalyst is a supported catalyst in which an alkali metal in the form of oxidation and / or sulfide has been applied to a carrier comprising zirconium dioxide and / or titanium dioxide. In that case, an impregnation aqueous solution containing a compound of an alkali metal in the form of oxidation and / or sulfide is directly impregnated onto the carrier to prepare a catalyst in the form of a supported catalyst. The carrier is not limited in specific size. For example, it can be present in a powder form with a particle size of less than 1000 μm, less than 500 μm, at most 250 μm such as 125 to 250 μm, or at most 125 μm such as 25 to 125 μm, the particle size being determined in a wet dispersion by laser scattering according to international standard ISO 13320 (2009). Thus, the catalyst according to the invention may also be in the form of extrudates or pellets obtained by impregnating a powder support with an aqueous solution containing a compound comprising an alkali metal in oxidic and / or sulphide form, followed by drying and calcination, wherein the calcination converts the alkali metal in oxidic and / or sulphide form into an alkali metal oxide. The catalytic mass thus obtained is mixed with a binder and shaped to provide a complete catalyst. Typically, the catalyst thus obtained is again subjected to calcination (in which any binder is burned off), optionally followed by a tempering step at a temperature of 100 to 200° C.
[0025] In a further embodiment, the catalyst according to the invention is a full catalyst.
[0026] When producing a core-shell catalyst, the powder support described above is impregnated with an aqueous solution containing a compound containing an alkali metal in the form of an oxide and / or sulfide. The mixture thus obtained is optionally calcined, mixed with a binder and applied in the form of spheres to an inert support core (for example made of ceramic), then calcined and optionally tempered to obtain a core-shell catalyst.
[0027] In another embodiment, the catalyst according to the invention is a core-shell catalyst.
[0028] The catalyst according to the invention requires only the presence of alkali metal in oxidized and / or sulfided form on the support, and not necessarily the presence of compounds containing tungsten in oxidized form, such as tungstic acid or tungstates. This also significantly simplifies the preparation of the catalyst compared to the prior art processes, in which a specific ratio of alkali to tungsten must be met.
[0029] Another object of the present invention is a process for preparing the catalyst according to the present invention, comprising the following steps:
[0030] a) impregnating a support comprising or consisting of titanium dioxide, zirconium dioxide and / or mixtures thereof with an aqueous solution comprising a soluble alkali compound to provide an impregnated support,
[0031] b) drying the impregnated support obtained from step a), and
[0032] c) calcining the dried impregnated support obtained from step b) to provide a catalyst.
[0033] In order to apply the impregnation solution to the support, various impregnation techniques can be used, such as immersion impregnation, spray impregnation, vacuum impregnation and pore volume impregnation. This also allows the impregnation to be performed more than once. In the case of a molded part, the selected impregnation method must be able to apply the required amount of promoter with good uniformity over the entire cross section of the molded part. The impregnation solution is preferably applied to the molded part in one or two steps by spraying or vacuum impregnation. In spray impregnation, an aqueous impregnation solution is sprayed onto the support. In vacuum impregnation, a vacuum pump is used to generate a reduced pressure in a container containing the molded part. By opening the connection with the aqueous impregnation solution, the solution is sucked into the container until the entire charge of the molded part is covered by the solution. After an impregnation period of 0.2 to 2 hours, the solution that is not absorbed by the material is discharged or poured out. By pre-drying at room temperature for 1 to 10 hours, the initial concentration gradient on the cross section of the molded part can be largely balanced. Therefore, the impregnation uniformity on the cross section of the catalyst particles is improved. The catalyst precursor thus obtained is preferably dried overnight, for example at 50 to 100° C., preferably at 60 to 80° C., for 1 to 10 hours, to remove residual moisture. Calcination is then carried out at 300 to 600° C., preferably at 420 to 480° C., for 1 to 20 hours, preferably 1 to 5 hours. As a result, the alkali metal in the form of oxidation and / or sulfide from the impregnation solution is transferred to the alkali metal oxide as a promoter, which is fixed on the support, and the anions from the impregnation solution are destroyed and driven off. During drying and calcination, a gas stream can optionally be passed through the charge of the support for the catalyst precursor, which improves the removal of residual moisture and decomposition gases. Deviations from the explicitly mentioned values for the period and temperature of the calcination are within the scope of the invention, as long as they lead to the same effect quality as the explicitly mentioned values.
[0034] The process according to the invention is not restricted in the choice of the alkali metal compound in the impregnation solution. The only requirement is that the alkali metal compound must have sufficient solubility in water so that the support is loaded with the desired concentration of alkali metal and that the anion is easily decomposed during the calcination step. It is therefore preferred to use alkali metal hydroxides, alkali metal acetates, alkali metal carbonates or alkali metal nitrates.
[0035] Nevertheless, alkali metal compounds with relatively low solubility in water can also be used. When the low solubility of the alkali metal compound in water does not allow the desired alkali metal loading to be obtained in a single impregnation step, the impregnation of the support can also be carried out in multiple steps, in particular in two steps. For example, the impregnation solution used in the first step then contains one-third to two-thirds of the total amount of the alkali metal compound comprising the oxidized and / or sulfide form, the remaining amount being applied to the support in the second step or any further step. In multiple steps, for example in a two-step procedure, the intermediate product obtained in the first step is optionally not calcined. Apart from this, the same impregnation, drying and calcination procedure as described for the one-step process is carried out in the second step.
[0036] In one embodiment of the process for preparing the catalyst according to the invention, steps a) to b) or a) to c) are repeated at least once.
[0037] The catalyst thus obtained, in particular the catalyst obtained from step c), can be mixed with a binder and then subjected to a shaping process such as extrusion or pelletization to obtain the full catalyst. The extrudate or pellets thus obtained are subjected to final calcination and optionally tempering.
[0038] In another embodiment, the method for preparing the catalyst further comprises the steps of:
[0039] d1) shaping the catalyst obtained in step c) of the process for preparing the catalyst to obtain a whole catalyst.
[0040] Alternatively, the catalyst from step c) can also be applied to a core to obtain a core-shell catalyst. To this end, the catalyst obtained from step c) is suspended in a solvent, preferably water, mixed with a binder, and the mixture thus obtained is applied to an inert core (for example, made of a ceramic material), for example by spray drying, followed by calcination to remove the solvent and burn off the binder, and optionally tempering.
[0041] In an alternative embodiment, the method for preparing the catalyst further comprises the steps of:
[0042] d2) applying the catalyst obtained in step c) of the process for preparing the catalyst to a core to provide a core-shell catalyst.
[0043] The catalyst according to the invention and the catalyst obtained by the process according to the invention are suitable for the catalytic reaction of alkyl alcohols with hydrogen sulfide to give alkyl mercaptans, which is also called alkyl alcohol mercaptation.
[0044] A further object of the present invention is therefore a process for preparing alkyl mercaptans, wherein an alkyl alcohol is reacted with hydrogen sulfide in the presence of a catalyst according to the invention or a catalyst obtainable by a process according to the invention.
[0045] In principle, the mercaptification process according to the invention is not restricted to the use of specific alkyl alcohols or to the preparation of specific alkyl mercaptans. However, the most economically relevant alkyl alcohol is methyl mercaptan.
[0046] In an embodiment of the mercaptification process according to the invention, the alkyl alcohol to be reacted is therefore methanol and the alkyl mercaptan to be prepared is methyl mercaptan.
[0047] The present invention is further described by the following items:
[0048] 1. A catalyst comprising a support and a promoter, wherein the support comprises titanium dioxide, zirconium dioxide and / or a mixture thereof, and the promoter is an alkali metal in the form of an oxide and / or a sulfide.
[0049] 2. The catalyst according to item 1, wherein at least a portion of the support has a tetragonal phase.
[0050] 3. The catalyst according to item 1 or 2, wherein the promoter is an alkali metal oxide and / or an alkali metal sulfide.
[0051] 4. The catalyst according to any one of items 1 to 3, wherein the alkali metal is sodium, potassium, cesium or rubidium.
[0052] 5. The catalyst according to any one of items 1 to 4, wherein the catalyst comprises up to 25% by weight of a promoter, based on the total weight of the catalyst.
[0053] 6. The catalyst according to any one of items 1 to 5, wherein the catalyst comprises 5 to 20% by weight of a promoter, based on the total weight of the catalyst.
[0054] 7. The catalyst according to any one of items 1 to 6, wherein the promoter is cesium oxide and / or cesium sulfide, and the catalyst comprises 5 to 20% by weight of the promoter, based on the total weight of the catalyst.
[0055] 8. The catalyst according to any one of items 1 to 7, wherein the catalyst is a full catalyst.
[0056] 9. The catalyst according to any one of items 1 to 8, wherein the catalyst is a core-shell catalyst.
[0057] 10. A method for preparing a supported catalyst according to any one of items 1 to 7, comprising the following steps:
[0058] a) impregnating a support comprising titanium dioxide, zirconium dioxide and / or a mixture thereof with an aqueous solution comprising a soluble alkaline compound,
[0059] b) drying the impregnated support obtained from step a), and
[0060] c) calcining the dried impregnated support of step b) to provide a catalyst.
[0061] 11. The method according to item 10, wherein steps a) to c) are repeated at least once.
[0062] 12. The method according to item 10 or 11, further comprising the following steps:
[0063] d1) shaping the catalyst obtained from step c) to obtain a whole catalyst.
[0064] 13. The method according to item 10 or 11, further comprising the following steps:
[0065] d2) applying the catalyst obtained from step c) to a core to provide a core-shell catalyst.
[0066] 14. A process for preparing alkyl mercaptan, wherein an alkyl alcohol is reacted with hydrogen sulfide in the presence of a catalyst according to any one of items 1 to 9 or a catalyst obtained by a process according to any one of items 10 to 13.
[0067] 15. The process according to item 14, wherein the alkyl alcohol to be reacted is methanol and the alkyl mercaptan to be prepared is methyl mercaptan. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 Shown are the XRD patterns of pure metal oxide (a) and metal oxide loaded with 5 wt% Cs (b), 10 wt% Cs (c), 15 wt% Cs (d) and 20 wt% Cs (e), where γ represents the characteristic signal of pure γ-Al2O3, t represents tetragonal ZrO2, A represents anatase (TiO2), and Cs represents Cs2CO3.
[0069] Figure 2 The following is a subtraction infrared spectrum of pyridine absorbed on pure metal oxide at 50°C, wherein the solid line represents the infrared spectrum taken at a pyridine partial pressure of 0.1 mbar and the broken line represents the infrared spectrum taken at a pyridine partial pressure of 10 -7 Infrared spectrum taken after evacuation at 100 mbar.
[0070] Figure 3 The following are the differential spectra of the OH vibration region of γ-Al2O3, ZrO2 and TiO2, where the solid line represents the infrared spectrum taken at a pyridine partial pressure of 0.1 mbar and the broken line represents the infrared spectrum taken at a pyridine partial pressure of 10 -7 Infrared spectrum taken after evacuation at 100 mbar.
[0071] Figure 4The following are the subtraction infrared spectra of metal oxides with Cs loading of 10 or 20 wt % at 50° C., wherein the solid line represents the infrared spectrum taken at a pyridine partial pressure of 0.1 mbar, and the broken line represents the infrared spectrum taken at a pyridine partial pressure of 10 -7 Infrared spectrum taken after evacuation at 100 mbar.
[0072] Figure 5 Shown are infrared spectra of CO adsorption on γ-Al2O3 (left), ZrO2 (middle) and TiO2 (right) at a CO partial pressure of 5 mbar and at -150°C, where (a) pure metal oxides, (b) Cs loading is 10 wt%, and (c) Cs loading is 20 wt%.
[0073] Figure 6 Shown are infrared spectra of methanol adsorbed on Al2O3 (left), ZrO2 (middle) and TiO2 (left) at a methanol partial pressure of 0.1 mbar and at 50°C, where (a) are pure metal oxides, (b) Cs loading is 10 wt%, and (c) Cs loading is 20 wt%.
[0074] Figure 7 Shown are infrared spectra of methanol absorption on pure metal oxides γ-Al2O3 (left), ZrO2 (middle) and TiO2 (right) at methanol partial pressures and temperatures of (a) 50°C and 0.1 mbar, (b) 50°C and 1 mbar, (c) 100°C and 1 mbar, (d) 150°C and 1 mbar, (e) 200°C and 1 bar, (f) 250°C and 1 mbar, and (g) 300°C and 1 mbar.
[0075] Figure 8 Shown are infrared spectra of methanol on γ-Al2O3 containing 10 wt% and 20 wt% Cs (left), ZrO2 containing 10 wt% and 20 wt% Cs (middle), and TiO2 containing 10 wt% and 20 wt% Cs (right) at methanol partial pressures and temperatures of (a) 50°C and 0.1 mbar, (b) 50°C and 1 mbar, (c) 100°C and 1 mbar, (d) 150°C and 1 mbar, (e) 200°C and 1 mbar, (f) 250°C and 1 mbar, and (g) 300°C and 1 mbar.
[0076] Fig. 9 Shown are the initial rates of methyl mercaptan formation on γ-Al2O3 (left), ZrO2 (middle), and TiO2 (right) at temperatures between 300 and 360°C for pure metal oxides (solid line with cubes), 10 wt% Cs loading (dashed line with circles), and 20 wt% Cs loading (broken line with triangles).
[0077] Fig.10Shown are the yields of methyl mercaptan (cubes), dimethyl ether (circles) and dimethyl sulfide (triangles) as a function of methanol conversion at 360°C on the pure metal oxides γ-Al2O3 (left), ZrO2 (center) and TiO2 (right).
[0078] Fig.11 Shown are the yields of methyl mercaptan (cubes), dimethyl ether (circles), and dimethyl sulfide (triangles) as a function of methanol conversion on γ-Al2O3 containing 10 wt% and 20 wt% Cs (left), ZrO2 containing 10 wt% and 20 wt% Cs (center), and TiO2 containing 10 wt% and 20 wt% Cs (right) at temperatures between 300 and 360°C.
[0079] Fig.12 Shown is the dependence of the methyl mercaptan formation rate on γ-Al2O3 in methanol (cubes; y = 0.3x + 1.7) and hydrogen sulfide (triangles; y = 0.5x + 1.9), ZrO2 in methanol (cubes; y = 0.2x–0.3) and hydrogen sulfide (triangles; y = 0.4x–0.6), and TiO2 in methanol (cubes; y = 0.3x + 1.2) and hydrogen sulfide (triangles; y = 0.5x + 1.7), with concentrations in mol / l.
[0080] Fig.13 Shown is the dependence of the methyl mercaptan formation rate on catalysts with different cesium loadings: 10 wt. % Cs (first row), in methanol represented by cubes (γ-Al2O3: y = 0.4x + 1.0; ZrO2: y = 0.5x + 1.5; and TiO2: y = 0.6x + 2.3), and in hydrogen sulfide represented by triangles (γ-Al2O3: y = 0.4x + 0.6; ZrO2: y = 0.3x - 0.01; and TiO2: y = 0.2x + 0.2). 20 wt.% Cs (second row) in methanol represented by cubes (γ-Al2O3: y = 0.3x + 1.0; ZrO2: 0.6x + 2.3; and TiO2: y = 0.5x + 2.0), and in hydrogen sulfide represented by triangles (γ-Al2O3: y = 0.5x + 1.3; ZrO2: y = 0.3x + 0.5; and TiO2: y = 0.2x + 0.3), concentrations are expressed in mol / l.
[0081] Fig.14Shown is the dependence of the dimethyl ether formation rate on pure γ-Al2O3 in methanol (represented by cubes; y=1.5x+11.0) and in hydrogen sulfide (represented by triangles, y=0.0x), on pure ZrO2 in methanol (represented by cubes; y=0.7x) and on pure TiO2 (represented by cubes; y=0.7x+2.3), the concentrations being expressed in mol / l.
[0082] Fig.15 Shown are the initial rates of methyl mercaptan formation on γ-Al 2 O 3 loaded with CsWS 2 (5.1 wt % tungsten content, 20.6 wt % cesium content) at temperatures of 300, 320, 340 and 360° C. (solid squares). Example
[0083] 1. Preparation of Cs-loaded metal oxides according to the present invention
[0084] Catalysts with Cs loadings of 5, 10, 15 and 20 wt% (based on the total weight of the catalyst) were prepared by incipient wetness impregnation of commercially available metal oxides γ-Al2O3 (Spheralite 101, Axens), TiO2 (Hombikat 100UV, Sachtleben) and ZrO2 (SZ 61152, Norpro), each having a crystallite size of 0.125-0.25 mm, with an aqueous solution of cesium acetate added dropwise to the stirred solids. For each Cs loading, a different impregnation solution containing the desired amount of cesium acetate was prepared to provide the desired Cs loading. 76 mg of cesium acetate (Sigma Aldrich, ≥99.99%) was dissolved in 0.5 mL H2O / 1 g of support to obtain 5 wt% Cs loading, 160.5 mg of cesium acetate for 10 wt% Cs loading, 255 mg of cesium acetate for 15 wt% Cs loading, and 361.0 mg of cesium acetate for 20 wt% Cs loading, respectively. The impregnated metal oxides were dried overnight at 70°C and subsequently calcined at 400°C for 2 hours in flowing synthetic air at a flow rate of 100 mL / min and at a ramp of 0.5°C / min. Before they were used in catalytic tests, all samples were activated by treating in H2S at a flow rate of 20 ml / min for 2 hours at 360°C.
[0085] 2. Characterization of the Prepared Catalysts
[0086] 2.1 Elemental composition and surface area determination
[0087] The elemental composition of the catalyst prepared according to the present invention was determined by atomic absorption spectroscopy (AAS). Measurements were performed on a UNICAM939AA-spectrometer. In order to determine the structural characteristics, N2 physical adsorption was performed on a BET-121 specific surface area analyzer of PMI (Porous Materials Inc.), USA. After activation at 250°C for 2 hours under vacuum, N2 was adsorbed at a temperature of 77.4K. The surface area was calculated using the BET method. The results of the elemental analysis and surface determination of all prepared catalysts are summarized in Table 1 below.
[0088]
[0089] Table 1: Results of elemental analysis and surface determination of all prepared catalysts
[0090] The results show that comparable Cs loadings were achieved for each of the three types of support materials. In general, the specific surface area of the prepared supported catalysts decreased with increasing Cs loading. This can be attributed to the increase in catalyst density and the coverage of the surface by Cs, both of which lead to a loss of surface area.
[0091] Table 2 below summarizes the different masses of cesium acetate in the different impregnation solutions used to prepare the catalysts, the Cs + The mass of the catalyst (support + Cs + ), Cs in the prepared catalyst + The theoretical concentration (C Th (M(cesium) / m(catalyst)), Cs in the prepared catalyst was found by elemental analysis + The concentration (C EA (M(cesium) / m(catalyst)).
[0092]
[0093] Table 2: Overview of the prepared catalysts and their cesium concentrations.
[0094] 2.2 Crystal structure
[0095] The crystal structures of all supports and all catalysts were determined by powder X-ray diffraction. XRD patterns were collected using a Philips X'Pert system (Cu Kα radiation, 0.1542 nm) operating at 45 kV / 40 mA, using a nickel Kβ filter and a solid-state detector (X'Celerator). Measurements were made using a step size of 0.017° and a scan time of 0.31 s / step.
[0096] The support materials gave the expected diffraction patterns, pure phase in γ-Al2O3, anatase in TiO2, and tetragonal zirconia in ZrO2. Figure 1 As shown. After the addition of Cs, the crystal structure of the support material did not change, showing the same diffraction pattern. Additional diffraction peaks indicative of Cs2CO3 were observed on γ-Al2O3 and TiO2 at 45°C. The carbonate is believed to be formed by the reaction of surface Cs species with atmospheric CO2. After sulfidation, the carbonate and its peaks disappear, resulting in the formation of sulfide anions that cannot be detected by X-ray diffraction. No other reflections appear. It is therefore concluded that the active Cs species is XRD amorphous.
[0097] 2.3 Characterization of acid-base properties
[0098] The adsorption of CO and pyridine onto the pure metal oxides and the prepared catalysts was monitored by infrared spectroscopy in transmission absorption mode (sample pressed into a self-supporting wafer) to measure Lewis acidity. Prior to adsorption, the sample was heated to 360°C at a ramp rate of 10°C / min under a flow of 10 mL / min of helium. Subsequently, the sample was sulfided at 360°C for 0.5 h under a flow of 10 mL / min of 10% vol% hydrogen sulfide in nitrogen. To remove physically adsorbed hydrogen sulfide, the sample was evacuated to 10 °C before being evacuated to 10 °C. -7 The sample was purged with a 10 mL / min He flow for an additional 15 min before being evacuated to 10 mbar and cooled to 50°C. For pyridine adsorption, the sample cell was cooled to 50°C and the sample was exposed to pyridine at a 1 mbar pyridine partial pressure, which was then reduced. The vacuum was further evacuated to 10 -5 mbar resulted in no pyridine adsorption on the Cs-containing samples. Therefore, the spectra of the different catalysts were compared at 0.1 mbar before evacuation. The concentration of the coordinated pyridine was calculated using the molar integrated extinction coefficient of 0.96 cm / μmol, which is calculated for the 1450 cm -1 The characteristic bands at 1000 nm were determined. CO adsorption was performed by cooling the IR cell to -150° C. using liquid nitrogen. The spectra were recorded at a CO partial pressure of 5 mbar.
[0099] Methanol was adsorbed at 50°C while increasing the methanol partial pressure stepwise (0.1 mbar, 0.5 mbar, 1 mbar and 5 mbar), followed by increasing the temperature to 300°C. All spectra were recorded with a Nicolet 6700 FTIR spectrometer (64 scans were collected to obtain each spectrum). All spectra were background subtracted and normalized to the mass of the wafer.
[0100] 2.4 Pyridine absorption
[0101] The acidity of metal oxides was measured by infrared absorption of pyridine. Figure 2On pure γ-Al2O3, the peaks at 1621, 1612, 1591, 1577, 1450 and 1440 cm -1 Eight bands were observed at 1621 and 1612 cm -1 The band at 1579 cm-1 is assigned to the 8a vibration mode of pyridine coordinated to Lewis acid sites (LAS) of different acid strengths (the wave number increases with the acid strength), while the band at 1579 cm-1 is assigned to the 8a vibration mode of pyridine coordinated to Lewis acid sites (LAS) of different acid strengths (the wave number increases with the acid strength). -1 The band at 1591cm is assigned to the 8b vibration mode. -1 The band at 1450 cm-1 is assigned to the 8a vibration mode of H-bonded pyridine caused by the interaction of pyridine with weakly acidic surface hydroxyl groups. -1 The signal at 1440 cm is attributed to the 9b vibration of pyridine on LAS, while the -1 The band at 1450 cm-1 is again assigned to pyridine H-bonded on the hydroxyl group. The band at 1450 cm-1 is assigned to the site of pyridine coordinated to LAS. -1 , 1612-1620cm -1 ) is stable to vacuum, while the H-bonded pyridine bands (1440 and 1593 cm -1 ) disappears after evacuation due to its weak interaction with the probe molecule. This is consistent with the release of OH groups, resulting in the 3700 cm -1 The negative OH band around the region decreases because the H-bonded pyridine is desorbed ( Figure 3 ).
[0102] By infrared spectroscopy, the adsorption of pyridine on ZrO2 and TiO2 was confirmed at 1604, 1593, 1573 and 1445 cm -1 The band produced at 1604cm -1 The 8a vibration mode of pyridine bound to LAS in ZrO2 and TiO2 is assigned, while 1573 cm -1 Assigned to 8a vibration mode. 1593cm -1 Assigned to the 8a vibrational mode of H-bonded pyridine caused by the interaction of pyridine with weakly acidic surface hydroxyls. As in the case of γ-alumina, this signal disappears after evacuation. 1445 cm -1 The signal at 1450 cm-1 is assigned to the 9b vibration of pyridine on LAS. -1 The spectral band was integrated at 454 μmol g on the metal oxide, and the LAS concentration on γ-Al2O3 was determined to be 454 μmol g -1 , 220 μmol g on ZrO2 -1 and 749 μmol g on TiO2 -1 The pyridine signal is from γ-Al2O3 (1450cm -1 ) to ZrO2 and TiO2 (1445cm -1) to lower wavenumbers indicates that the former has higher Lewis acid strength than the latter.
[0103]
[0104] Table 3: Summary of all discussed metal signals and their assignments.
[0105] Adding Cs to metal oxides changes the infrared spectra with adsorbed pyridine ( Figure 4 ). On medium-doped γ-Al2O3 and Cs(10) / γ-Al2O3, the peaks assigned to the strong (1612 cm -1 ) and weak (1609cm -1 ) The band of the 8a vibration mode of pyridine bound by LAS coordination, as well as the signal of H-bonded pyridine. At 1583 cm -1 A new band appears at , which corresponds to Cs with weak Lewis acids and bases, i.e., Lewis acids with lower strength than those measured on γ-Al2O3. + The 8a vibration mode of pyridine is coordinated by the addition of Cs to ZrO2 and TiO2, Cs(10) / ZrO2, and Cs(10) / TiO2. No bands assigned to the LAS of the support were observed. As in the case of Cs / γ-Al2O3, the band at 1600 cm -1 and 1583cm -1 New bands appeared at , corresponding to the 1+6a and 8a overtone vibration modes of pyridine on Cs. After vacuum evacuation, the pyridine signal on the Cs site disappeared on all three samples, but was partially retained on Cs(10) / γ-Al2O3 and Cs(10) / TiO2.
[0106] The other Cs and Cs(20) / γ-Al2O3 lead to 1612 cm -1 At 1600cm -1 A new signal assigned to the 1+6a overtone vibration of pyridine on Cs was observed at 1583 cm -1 8a vibration and pyridine at 1573 cm on LAS and Cs -1 8b vibration. Therefore, the gradual addition of Cs to the γ-Al2O3 surface resulted in the strong LAS from γ-Al2O3 being replaced by the weaker LAS from Cs. The adsorption of pyridine on the Cs(20) / ZrO2 and Cs(20) / TiO2 catalysts only resulted in the + Pyridine is coordinated to sites (8a, 8b, and 1+6a). All adsorbed pyridine species on Cs-doped ZrO2 and TiO2 desorb under vacuum; whereas a small signal of LAS on Cs(20) / γ-Al2O3 remains.
[0107]
[0108]
[0109] Table 4: Partitioning of pyridine uptake on Cs-supported metal oxides.
[0110] Titration of the acidic sites with pyridine indicated a high heterogeneity of LAS sites in γ-Al2O3 with two types of LAS, whereas TiO2 and ZrO2 provided only one LAS with similar intensity on both materials, consistent with those observed in the literature. The effect of Cs deposition can be rationalized as follows: at moderate Cs loadings, Cs + The surface sites of the metal oxide are changed by direct interaction, increasing the surface basicity. This direct interaction is through the surface protons and Cs + This is accomplished by cation exchange.
[0111] At high Cs loadings, the surface is dominated by Cs. As assumed for potassium on TiO2, high base loadings lead to complete coverage of the metal oxide surface, resulting in surface properties similar to bulk basic materials.
[0112] 2.5 CO absorption
[0113] Figure 5 The CO adsorption of the catalysts by infrared is shown. The assignment of the different CO bands is shown in Table 4. Similar infrared bands were obtained when CO was adsorbed on different metal oxides. -1 The band between 2150 cm -1 Those nearby are assigned to surface hydroxyl groups. CO stretching vibration in γ-Al2O3 (2188 cm -1 ) is higher than ZrO2 (2177cm -1 ) and TiO2(2181cm -1 ) at higher wavenumbers, indicating a higher perturbation of the CO bond. This trend is the same as that observed with pyridine, implying a higher intensity of the Lewis acid sites of γ-Al2O3.
[0114] The addition of 10 wt% Cs on the three supports resulted in the reduction of the CO stretching vibration on LAS to lower wavenumbers (2138–2136 cm -1 ), which corresponds to adsorption on Cs + ions. In the case of Cs(10) / γ-Al2O3, at 2179 cm -1Additional bands appeared at , which correspond to LAS in the γ-Al2O3 support modified by alkaline cations. No bands for CO adsorbed on OH groups were observed. On the sample with a high Cs loading of 20 wt%, only signals for CO on Cs cations and physically adsorbed CO were detected. CO was not adsorbed on the Cs(20) / ZrO2 sample.
[0115] The red shift of the CO stretching vibration on LAS with Cs on the γ-Al2O3 surface is due to the increase in basicity, which reduces the Sanderson electronegativity. The results for TiO2 and ZrO2 are consistent with those for pyridine adsorption, where there are no accessible LAS on these materials at 10 wt% Cs loading. As in the case of pyridine adsorption, Cs + is the only substance available for CO adsorption on highly Cs-doped materials. CO adsorption by IR is consistent with pyridine adsorption; except for Cs(10) / γ-Al2O3, the Lewis acid sites of the supports are absent at 10 wt% Cs loading.
[0116]
[0117] Table 5: Partitioning of CO uptake on pure and Cs-loaded metal oxides.
[0118] 2.6 Methanol Absorption
[0119] The infrared spectra of methanol adsorbed on metal oxides and their Cs doping are as follows: Figure 6 As shown, 3000-2750cm -1 Region (alkyl (sp 3 )CH vibration) band. Between 3000-2900cm -1 The area between is allocated to (υ as (CH3)) or its asymmetric stretching with CH3 deformation vibration (2δ s (CH3)) while the lower band is assigned to the symmetric stretching vibration (υ s (CH3)). For υ at 50°C as and s Different intensities of the infrared bands assigned to methanol adsorption on strong Lewis acid sites and strong Lewis base sites were observed ( Figures 6 to 8 ). The former site leads to the formation of a bridged methoxide, referred to as species I, where for υ as (2943, 2948 and 2944 cm for γ-Al2O3, ZrO2 and TiO2 -1 ) and s (2845, 2852 and 2844 cm for γ-Al2O3, ZrO2 and TiO2 -1), the infrared bands are all at higher wavenumbers. as (2939, 2931 and 2923 cm for γ-Al2O3, ZrO2 and TiO2 -1 ) and s (2821, 2827 and 2821 cm for γ-Al2O3, ZrO2 and TiO2 -1 ), the latter site leads to the formation of ethanolate (dissociation of the OH group), referred to as species II. On ZrO2, relatively high concentrations of dissociated methanol can be seen, which increase further for TiO2. In the case of γ-Al2O3, heating of the IR unit leads to an increase in the intensity of the bridged methoxide (species I). No major changes were observed upon heating in the other two supports. The relative intensity of methanol on the surface species directly leads to the conclusion that the general acidic character of the metal oxides relative to more basic metal oxides decreases in the order γ-Al2O3>ZrO2~TiO2.
[0120] 3. Catalytic testing of supported catalysts according to the present invention
[0121] The catalytic mercaptation of methanol was carried out in a reaction tube with a volume of 25 mL. Before the reaction, 125.0 mg of catalyst (125-250 μm) diluted in 1 g of SiC was heated at 360 °C and 9 bar in 20 mL min -1 The volume of the catalyst is almost negligible compared to the void volume of the plug flow reactor (20 mL). This results in only 0.054 h -1 The relatively low liquid hourly space velocity (LHSV) based on liquid methanol (CH3OH) and the gas hourly space velocity (GHSV) based on the complete feed (H2S, CH3OH and N2) is 150h -1 (Based on standard conditions of 0 °C and 1.013 bar, according to DIN 1343). To determine the activation energy, a mixture of H2S (20 mL min -1 ) and N2 (20 mL min -1 ) of gaseous CH3OH (10 mL min -1 ) stream was reacted at a feed stream pressure of 9 bar with a N2 partial pressure of 3.6 bar, a H2S partial pressure of 3.6 bar and a methanol partial pressure of 1.8 bar. The reaction tube was heated to a temperature between 300 and 360° C. by means of a heat transfer medium through a jacket.
[0122] Standard calculations of the Weisz–Prater modulus showed that it was <1 for all catalysts under all conditions, so it can be concluded that the kinetic results are not affected by internal mass transfer effects. The product streams were analyzed on-line using a Shimadzu GC-2014 equipped with an HP plot Q column (2.7 m, 2.0 mm i.d.) with a TCD detector. The reaction rate constants were calculated using the integrated rate law for the 0.5 order reaction of CH3OH and H2S for CH3SH. In order to study the product distribution over the entire conversion range, the residence time was adjusted so that the partial pressure of CH3OH was kept at 2.2 bar and the partial pressures of N2 and H2S were kept at 3.3 bar at 360 °C.
[0123] The reaction order was determined at 360°C. For the reaction order of H2S, the partial pressure of methanol was kept constant at 2.2 bar, while the partial pressure of H2S was varied between 1.1 bar and 5.6 bar. To measure the methanol reaction order, the H2S partial pressure was set to 4.5 bar, while the CH3OH partial pressure was varied from 0.6 mbar to 2.2 gaseous CH3OH. The N2 gas flow was adjusted to compensate for the volume flow variation and the total volume flow was kept constant at 80 ml / min. The amount of catalyst used in each experiment was adjusted accordingly to ensure that the CH3OH conversion was less than 10%. The reaction order of the cesium-modified materials was measured with 10.0 mg of catalyst, while 5.0 mg of TiO2 and ZrO2 and 1.0 mg of γ-Al2O3 were sufficient. In the case of γ-Al2O3, the catalyst was physically mixed with SiO2 in a ratio of 1:9, which is inert in the reaction studied to avoid channeling.
[0124] 3.1 Catalytic activity
[0125] The initial rate of formation of methyl mercaptan (CH3SH) is as follows Fig. 9 It was observed that TiO2 had the highest methanol thiolation rate (0.17-1.4·10 -6 mol CH3SH s -1 g cat -1 ), followed by γ-Al2O3 (0.13-9.2·10 -6 mol CH3SH s -1 g cat -1 ) and ZrO2(0.02-0.2·10 -6 mol CH3SH s -1 g cat -1For the Cs-doped system, the rate of CH3SH formation is Cs (10 wt%) / γ-Al2O3 (1.8-8.7·10 -6 mol CH3SH s -1 g cat -1 )>Cs(10wt%) / ZrO2(1.7-7.1·10 -6 mol CH3SH s -1 g cat -1 g cat )>Cs(10wt%) / TiO2(1.8-6.6·10 -6 mol CH3SH s -1 g cat -1 ) in the order of 20 wt %. A higher Cs loading of 20 wt % does not lead to higher catalyst activity; rather, the activity is higher for Cs (20 wt %) / γ-Al2O3 (2.0-7.6·10 -6 mol CH3SH s -1 g cat -1 )、Cs(20wt%) / ZrO2(1.7-7.1·10 - 6 mol CH3SH s -1 g cat -1 ) and Cs(20wt%) / TiO2(1.8-5.8·10 -6 mol CH3SH s -1 g cat -1 ). While there is an order of magnitude difference in the CH3SH formation rate with the different metal oxides, the activity of the Cs system shows only minor differences. This suggests that the overall activity is determined by the surface Cs species, which appear to be similar on all three metal oxide supports. In fact, the CH3SH formation rate is slightly decreased for all three systems.
[0126] The yields of methyl mercaptan, dimethyl sulfide (DMS), and dimethyl ether (DME) were measured as a function of methanol conversion at 360 °C for all three metal oxides ( Fig.10)。Over γ-Al2O3, CH3SH and (DME) are obtained as primary products, with DME being the highest primary product up to a methanol conversion of 60%. Beyond a 60% conversion, the yield of DME drops to 20% at 90% conversion, and CH3SH is the main product. This behavior can be explained by the re-adsorption of DME on the catalyst, where secondary reactions occur to form CH3SH. Similar results are observed for ZrO2, where CH3SH is the main primary product and the dimethyl ether yield is below 10%. Notably, on ZrO2, no DME is formed at conversions below 10%. On γ-Al2O3 and ZrO2, dimethyl sulfide is found at higher conversion levels and is a secondary product in the formation of CH3SH. No dimethyl ether is observed on TiO2, and dimethyl sulfide is the only by-product. Conducting the reaction without H2S on ZrO2 and TiO2 leads to the formation of DME( Fig.10 ), which implies competition between the reactants on ZrO2 and TiO2. The yield of CH3SH increases in the order γ-Al2O3 < ZrO2 < TiO2. The yields of CH3SH, DMS, and DME are measured as a function of the CH3OH conversion at 360 °C for all three metal oxides with 10 wt% and 20 wt% Cs( Fig.11 )。The general trend for all Cs-containing systems is observed: CH3SH is obtained as the main product, and the only catalyst that produces DME is Cs(10 wt%) / Al2O3, where the DME yield at 360 °C is 0.3%. The main by-product is DMS, with a maximum yield of 0.7% on Cs(10 wt%) / Al2O3 at 360 °C. The absence of DME in the presence of Cs on the surface is attributed to the absence of strong LAS. These results are supported by pyridine and CO adsorption by infrared, indicating a significant reduction in Lewis acidity through Cs doping.
[0127] 3.2 Kinetics
[0128] a) Formation of methanethiol
[0129] The formation rate of methanethiol in methanol and hydrogen sulfide is dependent on Fig.12 the pure metal oxides in Fig.13 and the metal oxides with 10 wt% and 20 wt% Cs in
[0130]
[0131] Table 6: Reaction orders determined for the formation of methanethiol in H2S and CH3OH over all tested systems.
[0132] On all metal oxides, the reaction order of 0.5 for H2S and CH3OH in the formation of CH3SH suggests dissociation of the two reactants prior to the bimolecular Langmuir-Hinshelwood mechanism.
[0133] The rate equation for methyl mercaptan is
[0134]
[0135] Where a=(1+K2 0.5 [CH3OH] 0.5 +K3 0.5 [H2S] 0.5 +[CH3SH] 0.5 / K6 0.5 +[H2O] 0.5 / K7 0.5 ).
[0136] The rate equation for dimethyl ether is
[0137]
[0138] Where b = (1 + K1 0.5 [CH3OH] 0.5 +[H2O] 0.5 / K8 0.5 ).
[0139] It is known that hydrogen sulfide adsorbs dissociatively on the surface of metal oxides, while methanol also adsorbs dissociatively, forming methanolate on the Lewis acid-base pair of the surface oxide. Therefore, it is believed that both substrates dissociate on the same type of basic sites. It can be speculated that the decrease in the reaction order with partial pressure will produce an effect of competitive adsorption of substrates on the surface. However, this is not observed in the case of metal oxides.
[0140] The apparent activation energy for the formation of methyl mercaptan on γ-Al2O3 was found to be about 112 kJ mol -1 , about 115 kJmol on ZrO2 -1 , about 107 kJ mol on TiO2 -1 This is the apparent activation energy for the formation of methyl mercaptan on the active sites of the metal oxide since no Cs is present.
[0141]
[0142] Table 7: Apparent activation energies determined for the formation of methyl mercaptan.
[0143] The addition of Cs (10 wt%) resulted in a reaction order of nearly 0.5 for both reactants, suggesting the same dissociation reaction mechanism as proposed for pure metal oxides. However, the reaction order of 0.2 on H2S suggests that the Cs / TiO2 and Cs / ZrO2 catalysts operate under partial coverage of H2S. The apparent activation energy is reduced to 66 to 78 kJ mol -1 The lower activation energies of these catalysts relative to metal oxides are associated with increased basicity. + The presence of cations suggests a coverage of surface hydroxyl groups, similar to what has been observed for sodium and potassium on alumina. This was confirmed by the absence of OH bands confirmed by IR during pyridine and CO adsorption. Similar reaction order values were obtained for all highly Cs-doped (20 wt%) materials as for Cs 10 wt%, also suggesting a dissociation mechanism. The apparent activation barriers for the three highly doped materials ranged from 65 to 59 kJ mol -1 The decrease in the apparent activation energy can be explained by the complete modification of the surface. As shown for pyridine adsorption, the only surface species available during pyridine adsorption is Cs, which suppresses the metal oxide chemistry and acts as a very weak LAS. Moreover, the absence of strong Lewis acid sites leads only to the formation of surface methanolates, as observed by IR during methanol adsorption on highly Cs-doped catalysts.
[0144] The reaction orders of methanol and hydrogen sulfide for DME formation were determined for all pure metal oxides (Table 8 and Fig.14 ). On γ-Al2O, the reaction order in methanol for DME formation was 1.5 and the reaction order in H2S was 0. The zero order for H2S indicates that H2S does not compete with methanol on the DME formation sites. The 1.5 reaction order for methanol can be explained by the partial coverage of the catalyst surface by methanol. On γ-Al2O3, the adsorption of methanol appears to be favorable compared to H2S, leading to the formation of DMF and zero order for H2S. The reaction order for DME formation (in the absence of H2S) was found to be 0.7 on ZrO2 and TiO2. It is believed that the surface coverage of methanol is higher on these materials compared to γ-Al2O. The lower apparent activation energy on γ-Al2O3 compared to the other two materials is attributed to the higher Lewis acid strength, as shown by CO and pyridine adsorption, thereby promoting the breaking of the CO bond of CH3OH.
[0145]
[0146] Table 8: Reactions in methanol and hydrogen sulfide and apparent activation energies for dimethyl ether formation.
[0147] 3.3 Catalytic activity
[0148] For pure metal oxide catalysts, γ-Al2O3 has the lowest selectivity for methyl mercaptan formation, with dimethyl ether being the major product (with S DME,300℃ =71.2% and S DME,320℃ =63.4%). As the temperature increases, the selectivity for dimethyl ether decreases to S DME,340℃ =49.8% and the final S DME,360℃ = 28.6%. With the decrease of dimethyl ether selectivity, the methyl mercaptan selectivity increases from 28.5% at 300° C. to 71.2% at 360° C. The selectivity for dimethyl sulfide formation is less than 5%.
[0149] On pure ZrO2, the selectivity for the formation of methyl mercaptan was 53.1% at 300° C. and 60% at 360° C. Again, the main byproduct was dimethyl ether, but the selectivity decreased from 46.7% at 300° C. to 36.6% at 360° C. As with γ-Al2O3, the selectivity for dimethyl sulfide was less than 5%.
[0150] Among all the pure metal oxides, TiO2 provides the highest selectivity for methyl mercaptan formation: 96% at 300 °C, with the selectivity decreasing at higher temperatures (S DME,360℃ =79.2%). Compared with the other two metal oxides, the selectivity for dimethyl ether increases from S to DME,300℃ =4.0% increase to S DME,360℃ =16.6%). The production selectivity of dimethyl sulfide is less than 4%.
[0151] All Cs-supported catalysts showed a significant increase in CH3SH selectivity compared to the pure metal oxide catalysts. For 10 wt% Cs on γ-Al2O3, the selectivity of CH3SH formation increased to S CH3SH,300℃ =99.7% to S CH3SH,360℃ =98.3%. The selectivity of by-products increases with the increase of temperature: DME,300℃ =0.1% to S DME,360℃ = 0.5% selectivity to form DME, and S DMS,300℃ =0.2% to S DMS,360℃ = 1.2% selectivity to form DMS. Further increase of Cs loading to 20 wt% also increases CH3SH selectivity to as high as S CH3SH,300℃ =99.9% to S CH3SH,360℃ = 99.1% selectivity. In this case, the only by-product found was S DMS,300℃ =0.1% to S DMS,360℃ = 0.9% DMS.
[0152] For ZrO2-based catalysts, the selectivity for CH3SH increases to S CH3SH,300℃ =99.9% to S CH3SH,360℃ =99.1% range. Again, the only byproduct found was S DMS,300℃ =0.1% to S DMS,360℃ = 0.9% DMS. Increasing the Cs loading to 20 wt% resulted in a CH3SH,300℃ =99.9% and S CH3SH,360℃ = 99.4% or even higher selectivity.
[0153] Similar results were found for TiO2-based catalysts: in the case of 10 wt% Cs, the selectivity for CH3SH increased to between S CH3SH,300℃ =99.9% to S CH3SH,360℃ =99.4%. Again, the only byproduct found was S DMS,300℃ =0.1% to S DMS,360℃ = 0.6% dimethyl sulfide. Increasing the Cs loading to 20 wt% again resulted in a CH3SH,300℃ =99.9% and S CH3SH,360℃ = 99.5% or even higher selectivity.
[0154]
[0155] Table 9: Summary of product selectivities of prepared catalysts (nd = not detectable)
[0156] 4. Comparative Examples
[0157] Comparative example is carried out with the catalyst containing Cs2WS4 on γ-Al2O3. The catalyst is prepared by two-step initial wetness impregnation method. First, 5.0gγ-Al2O3 (similar to SPH 509 Axens, grain size is 150-250μm) is impregnated with 0.64g cesium acetate (Sigma Aldrich, ≥99.99%) dissolved in 1.6mL H2O. The sample is dried overnight at room temperature to obtain Cs / Al2O3. Next, the Cs2WS4 / Al2O3 system is synthesized as follows: Cs2WS4 crystals are formed by precipitation, and a solution of 350mg (NH4)2WS4 in 20ml H2O and a solution of 325mg Cs2CO3 in 20ml H2O are mixed. A yellow precipitate is formed. These solids are filtered and washed with ice-cold water and 1-propanol. Due to the low solubility of Cs2WS4, 450mg of these are dissolved in 150ml water. Then 2 g of Cs / Al2O3 was added to the solution. Water was removed by continuous rotary evaporation to precipitate Cs2WS4 crystals on the solid sample. The sample was dried overnight at room temperature. After drying, the sample was calcined at 455°C (heating rate of 5°C / min) for 4 hours. The prepared catalyst had a tungsten content of 5.1 wt%, a cesium content of 20.6 wt%, a 0.20 cm 3 g -1 The pore volume and 141m 2 g -1 The BET surface areas of the catalysts were measured as described above. A flow apparatus equipped with a mass spectrometer (QME 200, Pfeiffer Vacuum) was used with a pulse technique for adsorption, followed by temperature programmed desorption of H2S. A sample of the catalyst was loaded into a quartz reactor and activated in situ at 360°C for 2 hours at 4.2% by volume H2S / He at a flow rate of 6 ml / min. For H2S adsorption, the temperature was set to 360°C and the sample was purged with He for 1 hour before adsorption. A pulse of 4.4% by volume H2S in He (5.0 μmol / min of H2S) was introduced every 30 minutes. The total concentration of the adsorbed gas was calculated as the sum of the absorptions for each pulse.
[0158] The catalyst thus obtained was tested under the same reaction conditions and in the same reaction tube as in Example 3. Prior to the test, the catalyst was activated by treatment in H2S at a flow rate of 20 ml / min at 360°C for 2 hours.
[0159] The conversion of MeOH, the yields of CH 3 SH, DME and DMS, and the selectivity to CH 3 SH, DME and DMS at temperatures of 300° C., 320° C., 340° C. and 360° C. are summarized in Table 10 below.
[0160]
[0161] Table 10: Summary of the results of the comparative examples
[0162] The initial rate of CH3SH formation is Fig.15 The highest rate of methanol thiolation (1.34·10 -6 mol CH3SH s -1 g cat -1 ), and at higher temperatures have the following rates: at 360 ° C has the lowest rate (6.38 · 10 -6 mol CH3SH s -1 g cat -1 ).
Claims
1. A process for preparing alkyl mercaptan, wherein an alkyl alcohol is reacted with hydrogen sulfide in the presence of a catalyst, the catalyst comprising or consisting of a carrier and 5 to 20 wt % of a promoter, based on the total weight of the catalyst, wherein the carrier consists of titanium dioxide, zirconium dioxide and / or a mixture thereof, and the promoter is cesium oxide.
2. The process according to claim 1, wherein the alkyl alcohol to be reacted is methanol, and the alkyl mercaptan to be prepared is methyl mercaptan.
3. The method of claim 1, wherein at least a portion of the support has a tetragonal phase.
4. The method according to claim 1, wherein the support of the catalyst according to the invention consists of a tetragonal phase.
5. The method according to claim 1, wherein the catalyst is a whole catalyst, the whole catalyst is a catalyst obtained by shaping the catalyst of claim 1; or the whole catalyst is a catalyst obtained by mixing the catalyst of claim 1 with a binder and shaping it. The method of claim 1 , wherein the catalyst is a core-shell catalyst.
7. The method according to claim 6, wherein the amount is from 5 to 20% by weight with respect to the composition of the shell.
8. The process according to any one of claims 1 to 7, wherein the catalyst is prepared by a process comprising the steps of: a) impregnating a support consisting of titanium dioxide, zirconium dioxide and / or a mixture thereof with an aqueous solution comprising a soluble alkaline compound, b) drying the impregnated support obtained from step a), and c) calcining the dried impregnated support of step b) to provide said catalyst.
9. The method according to claim 8, wherein steps a) to c) are repeated at least once.
10. The method according to claim 8, further comprising the step of d1) shaping the catalyst obtained from step c) to obtain a whole catalyst, that is, the whole catalyst is a catalyst obtained by shaping the catalyst obtained from step c).
11. The method according to claim 10, further comprising the step of d2) applying said catalyst obtained from step c) to a core to provide a core-shell catalyst.
Citation Information
Patent Citations
Catalyst for the synthesis of alkyl mercaptan and process for the production thereof
US20090306432A1
Catalyst for the synthesis of alkyl mercaptans and process for producing it
US20140357897A1
Preparation of organic thiols
US2820062A
Catalyst, process for its preparation, and use for synthesis of methyl mercaptan
US5852219A
Catalyst for the synthesis of alkyl mercaptans and process for producing it
WO2013092129A1